Beneficios das plantas da capoeira para a comunidade de Benjamin Constant, Para, Amazonia Brasileira: The benefits of plants from secondary forests to the community of Benyamin Constant in Para State, Brazilian Amazon - Ríos, M.; Martins da Silva, R.C.V.; Sabogal, C.; Martins, J.; Silva, R.N. da; Brito, Guilherme R.R.; Brito, I.M. de; Costa de Brito, M.F.; Silva, J.R. da; Ribeiro, R.T. (Center for International Forestry Research, 2001)
Secondary forests, the woody successional vegetation which develops after the original vegetation of the site has been removed by human activity (usually for agriculture or livestock production), is a resource of growing importance in tropical landscapes. The community of Benjamin Constant, located in one of the oldest agricultural frontier areas in the Eastern Brazilian Amazon (the Bragantina Region in Para State), is inhabited by small-scale farmers practicing subsistence agriculture. As part of their livelihoods, families in this community rely on the existence of secondary forests. As a result of ethno-botanical studies carried out in the community, 135 useful plant species were identified, providing a wide array of products such as food, tubers, latex, oils, fibers, resins, gums, balsams, condiments, candles and cellulose. After two years of collaboration with the local population, a manual to valorize their traditional knowledge on forest plants was considered a priority. The present ethno-botanical manual describes 12 useful plants selected on the basis of intensity of local use and frequency of distribution. The species included are: amapá (Parahancornia fasciculata (Poir.) Benoist), anani (Symphonia globulifera L. f.), bacuri (Platonia insignis Mart.), barbatimão (Maytenus myrsinoides Reissek), caju (Anacardium occidentale L.), lacre (Vismia guianensis (Aubl.) Choisy), muruci-do-mato (Byrsonima aerugo Sagot), perpétua (Psychotria colorata (Willd. ex Roem. & Schult.) Müll. Arg.), piquiá (Caryocar villosum (Aubl.) Pers.), sapucaia (Lecythis pisonis Cambess.), siquiba (Himatanthus sucuuba (Spruce ex Müll. Arg.) Woodson) and verônica-vermelha (Dalbergia subcymosa Ducke). The work was part of the project Farmer Management of Secondary Forests (PBS), executed by Embrapa Amazônia Oriental (the Brazilian Enterprise for Agricultural Research – Research Station in the Eastern Amazon), FCAP (the Faculty of Agricultural Sciences of Para State) and CIFOR (the Center for International Forestry Research).